Philosophical pedagogy as critics and self- critics: german experience - Kultayeva Maria (Borys Grinchenko Kyiv Metropolitan University, 2017)
In the article are regarded some evolutional tendencies of philosophical pedagogy in the German theoretical tradition. The turn from the normative theories to functional-structuring ones is analyzed on the factual material of Neo-Hegelianism (E. Spranger, T. Litt) and on Adorno's half-education theory, where the half-education is represented as a form of educational alienation und contributes its conversion to anti-education. One of the alternative theoretical variants proposed by A. Tremlis deduced from theory of the self-referent social systems. Is showed that critics and self-critics of different philosophical and pedagogical constructs is giving impulses for development of philosophical pedagogy as a reflection of the inside logic of learning and educational practices including the claims of globalization. Despite numerous publications devoted to the problem of philosophical and pedagogical comprehension of the challenges of globalization that education is challenged with, the issue is still at an early stage. Nevertheless, the analysis shows that it has already made a certain contribution to the study of real and possible pathologies for the development of modern education. The findings of the research show that the reflection of the state and problems of education in philosophical pedagogy is, at the same time, always a test of the ability of pedagogical theories to fulfill their general civilization function. The activation of its ability to self-criticism is required to cope with that. Without the above mentioned factor, it can easily integrate into political ideology or adapt to the demands of the mass culture, turning from the guardian of the humanistic potential of education into its academically trained destroyer.